GAYA HIDUP PENGUNJUNG MP CLUB PEKANBARU - Septa Azura Ifwar; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Lifestyle are parents that distinguish between the actions of the others, Which is expressed in the activities, interests, and his opinions. Describes the overall lifestyle of a person in interacting with the environment. So that each individual will have their lifestyle. There is a positive lifestyle and negative lifestyle. Lifestyle visitor MP club included negative lifestyle. This study aims to give visitor an idea of how the characteristics of the MP club Pekabaru and how lifestyle visitor MP club Pekanbaru. This study uses the theory of lifestyle and social aberrations with books on lifestyle and social deviation. The research method used is descriptive qualitative. To know the results of the study, we used observation, interview, and documentation. As for the method of taking the subject of research by accidental sampling technique, wich is based on chance or anyone who met at the hall of the pub. Being the result is that all the informants in this research activity clubbing with pattersns in defiance of social norms that form a hedonistic lifestyle.Keywords: Characteristics, lifestyle, social deviation